Vision and Voyages for Planetary Science in the Decade 2013-2022 - National Research Council (The National Academies Press, 2011)
In recent years, planetary science has seen a tremendous growth in new knowledge. Deposits of water ice exist at the Moon's poles. Discoveries on the surface of Mars point to an early warm wet climate, and perhaps conditions under which life could have emerged. Liquid methane rain falls on Saturn's moon Titan, creating rivers, lakes, and geologic landscapes with uncanny resemblances to Earth's.
Keywords: Space and Aeronautics

Solar and Space Physics: A Science for a Technological Society - National Research Council (The National Academies Press, 2013)
From the interior of the Sun, to the upper atmosphere and near-space environment of Earth, and outward to a region far beyond Pluto where the Sun's influence wanes, advances during the past decade in space physics and solar physics—the disciplines NASA refers to as heliophysics—have yielded spectacular insights into the phenomena that affect our home in space. Solar and Space Physics, from the National Research Council's (NRC's) Committee for a Decadal Strategy in Solar and Space Physics, is the second NRC decadal survey in heliophysics. Building on the research accomplishments realized during the past decade, the report presents a program of basic and applied research for the period 2013-2022 that will improve scientific understanding of the mechanisms that drive the Sun's activity and the fundamental physical processes underlying near-Earth plasma dynamics, determine the physical interactions of Earth's atmospheric layers in the context of the connected Sun-Earth system, and enhance greatly the capability to provide realistic and specific forecasts of Earth's space environment that will better serve the needs of society. Although the recommended program is directed primarily at NASA and the National Science Foundation for action, the report also recommends actions by other federal agencies, especially the parts of the National Oceanic and Atmospheric Administration charged with the day-to-day (operational) forecast of space weather. In addition to the recommendations included in this summary, related recommendations are presented in this report.
Keywords: Space and Aeronautics; Math, Chemistry, and Physics

Earth Science and Applications from Space: A Midterm Assessment of NASA's Implementation of the Decadal Survey - National Research Council (The National Academies Press, 2012)
Understanding the effects of natural and human-induced changes on the global environment and their implications requires a foundation of integrated observations of land, sea, air and space, on which to build credible information products, forecast models, and other tools for making informed decisions. The 2007 National Research Council report on decadal survey called for a renewal of the national commitment to a program of Earth observations in which attention to securing practical benefits for humankind plays an equal role with the quest to acquire new knowledge about the Earth system. NASA responded favorably and aggressively to this survey, embracing its overall recommendations for Earth observations, missions, technology investments, and priorities for the underlying science. As a result, the science and applications communities have made significant progress over the past 5 years. However, the Committee on Assessment of NASA's Earth Science Program found that the survey vision is being realized at a far slower pace than was recommended, principally because the required budget was not achieved. Exacerbating the budget shortfalls, NASA Earth science programs experienced launch failures and delays and the cost of implementing missions increased substantially as a result of changes in mission scope, increases in launch vehicle costs and/or the lack of availability of a medium-class launch vehicle, under-estimation of costs by the decadal survey, and unfunded programmatic changes that were required by Congress and the Office of Management and Budget. In addition, the National Oceanic and Atmospheric Administration (NOAA) has made significant reductions in scope to its future Earth environmental observing satellites as it contends with budget shortfalls. Earth Science and Applications from Space: A Midterm Assessment of NASA's Implementation of the Decadal Survey recommends a number of steps to better manage existing programs and to implement future programs that will be recommended by the next decadal survey. The report also highlights the urgent need for the Executive Branch to develop and implement an overarching multiagency national strategy for Earth observations from space, a key recommendation of the 2007 decadal survey that remains unfulfilled.
Keywords: Space and Aeronautics; Earth Sciences

The Science of Planetary Exploration (The National Academies Press, 1979)
The Science of Planetary Exploration summarizes the knowledge of the solar system as of the late 1970s, and sets forth a strategy to guide solar-system exploration over the next decade. The summaries and recommendations are divided into three parts: the inner planets, the outer planets, and comets and asteroids. Exploration technology is also mentioned, including technologies that were currently under development. The report marks an important shift in how the Committee on Planetary and Lunar Exploration (COMPLEX) made recommendations. Formerly, the committee advised specific missions; but this report advises scientific goals instead as a more comprehensive and flexible strategy.
Keywords: Space and Aeronautics

Planetary Exploration, 1968-1975; Report of a Study by the Space Science Board, Washington, D.C., June 1968 - National Research Council (The National Academies Press, 1968)
Planetary Exploration, 1968-1975 is the report of a study convened by the Space Science Board to consider planetary exploration. The group reappraised the recommendations of the Board's 1965 Woods Hole Study in the light of advances in scientific knowledge and changing demands upon the nation's resources.
Keywords: Space and Aeronautics

The Astrophysical Context of Life - National Research Council (The National Academies Press, 2005)
In 1997, the National Aeronautics and Space Administration (NASA) formed the National Astrobiology Institute to coordinate and fund research into the origins, distribution, and fate of life in the universe. A 2002 NRC study of that program, Life in the Universe: An Assessment of U.S. and International Programs in Astrobiology, raised a number of concerns about the Astrobiology program. In particular, it concluded that areas of astrophysics related to the astronomical environment in which life arose on earth were not well represented in the program. In response to that finding, the Space Studies Board requested the original study committee, the Committee on the Origins and Evolution of Life, to examine ways to augment and integrate astronomy and astrophysics into the Astrobiology program. This report presents the results of that study. It provides a review of the earlier report and related efforts, a detailed examination of the elements of the astrobiology program that would benefit from greater integration and augmentation of astronomy and astrophysics, and an assessment of ways to facilitate the integration of astronomy with other astrobiology disciplines.
Keywords: Space and Aeronautics

NASA's Strategic Direction and the Need for a National Consensus - National Research Council (The National Academies Press, 2012)
The National Aeronautics and Space Administration (NASA) is widely admired for astonishing accomplishments since its formation in 1958. Looking ahead over a comparable period of time, what can the nation and the world expect of NASA? What will be the agency's goals and objectives, and what will be the strategy for achieving them? More fundamentally, how will the goals, objectives, and strategy be established and by whom? How will they be modified to reflect changes in science, technology, national priorities, and available resources? In late 2011, the United States Congress directed the NASA Office of Inspector General to commission a "comprehensive independent assessment of NASA's strategic direction and agency management." Subsequently, NASA requested that the National Research Council (NRC) conduct this independent assessment. In the spring of 2012, the NRC Committee on NASA's Strategic Direction was formed and began work on its task. The committee determined that, only with a national consensus on the agency's future strategic direction—along the lines described in the full NRC report—can NASA continue to deliver the wonder, the knowledge, the national security and economic benefits, and the technology that have been typified by its earlier history. NASA's Strategic Direction and the Need for a National Consensus summarizes the findings and recommendations of the committee.
Keywords: Space and Aeronautics

Panel Reports—New Worlds, New Horizons in Astronomy and Astrophysics - National Research Council (The National Academies Press, 2011)
Every 10 years the National Research Council releases a survey of astronomy and astrophysics outlining priorities for the coming decade. The most recent survey, titled New Worlds, New Horizons in Astronomy and Astrophysics, provides overall priorities and recommendations for the field as a whole based on a broad and comprehensive examination of scientific opportunities, infrastructure, and organization in a national and international context. Panel Reports—New Worlds, New Horizons in Astronomy and Astrophysics is a collection of reports, each of which addresses a key sub-area of the field, prepared by specialists in that subarea, and each of which played an important role in setting overall priorities for the field. The collection, published in a single volume, includes the reports of the following panels:
Keywords: Space and Aeronautics

Report of the Panel on Implementing Recommendations from the New Worlds, New Horizons Decadal Survey - National Research Council (The National Academies Press, 2012)
The 2010 Astronomy and Astrophysics Decadal Survey report, New Worlds, New Horizons in Astronomy and Astrophysics (NWNH), outlines a scientifically exciting and programmatically integrated plan for both ground- and space-based astronomy and astrophysics in the 2012-2021 decade. However, late in the survey process, the budgetary outlook shifted downward considerably from the guidance that NASA had provided to the decadal survey. And since August 2010—when NWNH was released—the projections of funds available for new NASA Astrophysics initiatives has decreased even further because of the recently reported delay in the launch of the James Webb Space Telescope (JWST) to no earlier than the fourth quarter of 2015 and the associated additional costs of at least $1.4 billion. These developments jeopardize the implementation of the carefully designed program of activities proposed in NWNH. In response to these circumstances, NASA has proposed that the United States consider a commitment to the European Space Agency (ESA) Euclid mission at a level of approximately 20 percent. This participation would be undertaken in addition to initiating the planning for the survey's highest-ranked, space-based, large-scale mission, the Wide-Field Infrared Survey Telescope (WFIRST).
Keywords: Space and Aeronautics

The Sun to the Earth -- and Beyond: A Decadal Research Strategy in Solar and Space Physics - National Research Council (The National Academies Press, 2003)
The sun is the source of energy for life on earth and is the strongest modulator of the human physical environment. In fact, the Sun's influence extends throughout the solar system, both through photons, which provide heat, light, and ionization, and through the continuous outflow of a magnetized, supersonic ionized gas known as the solar wind.
Keywords: Space and Aeronautics

New Worlds, New Horizons in Astronomy and Astrophysics - National Research Council (The National Academies Press, 2010)
Driven by discoveries, and enabled by leaps in technology and imagination, our understanding of the universe has changed dramatically during the course of the last few decades. The fields of astronomy and astrophysics are making new connections to physics, chemistry, biology, and computer science. Based on a broad and comprehensive survey of scientific opportunities, infrastructure, and organization in a national and international context, New Worlds, New Horizons in Astronomy and Astrophysics outlines a plan for ground- and space- based astronomy and astrophysics for the decade of the 2010's. Realizing these scientific opportunities is contingent upon maintaining and strengthening the foundations of the research enterprise including technological development, theory, computation and data handling, laboratory experiments, and human resources. New Worlds, New Horizons in Astronomy and Astrophysics proposes enhancing innovative but moderate-cost programs in space and on the ground that will enable the community to respond rapidly and flexibly to new scientific discoveries. The book recommends beginning construction on survey telescopes in space and on the ground to investigate the nature of dark energy, as well as the next generation of large ground-based giant optical telescopes and a new class of space-based gravitational observatory to observe the merging of distant black holes and precisely test theories of gravity. New Worlds, New Horizons in Astronomy and Astrophysics recommends a balanced and executable program that will support research surrounding the most profound questions about the cosmos. The discoveries ahead will facilitate the search for habitable planets, shed light on dark energy and dark matter, and aid our understanding of the history of the universe and how the earliest stars and galaxies formed. The book is a useful resource for agencies supporting the field of astronomy and astrophysics, the Congressional committees with jurisdiction over those agencies, the scientific community, and the public.
Keywords: Space and Aeronautics

One Universe: At Home in the Cosmos - Tyson, Neil de Grasse; Liu, Charles; Irion, Robert (The National Academies Press, 2000)
A new window opens onto the cosmos... Almost every day we are challenged by new information from the outermost reaches of space. Using straightforward language, One Universe explores the physical principles that govern the workings of our own world so that we can appreciate how they operate in the cosmos around us. Bands of color in a sunlit crystal and the spectrum of starlight in giant telescopes, the arc of a hard-hit baseball and the orbit of the moon, traffic patterns on a freeway and the spiral arms in a galaxy full of stars—they're all tied together in grand and simple ways. We can understand the vast cosmos in which we live by exploring three basic concepts: motion, matter, and energy. With these as a starting point, One Universe shows how the physical principles that operate in our kitchens and backyards are actually down-to-Earth versions of cosmic processes. The book then takes us to the limits of our knowledge, asking the ultimate questions about the origins and existence of life as we know it and where the universe came from—and where it is going. Glorious photographs—many seen for the first time in these pages—and original illustrations expand and enrich our understanding. Evocative and clearly written, One Universe explains complex ideas in ways that every reader can grasp and enjoy. This book captures the grandeur of the heavens while making us feel at home in the cosmos. Above all, it helps us realize that galaxies, stars, planets, and we ourselves all belong to One Universe.
Keywords: Explore Science; Space and Aeronautics

NASA Space Technology Roadmaps and Priorities: Restoring NASA's Technological Edge and Paving the Way for a New Era in Space - National Research Council (The National Academies Press, 2012)
NASA's Office of the Chief Technologist (OCT) has begun to rebuild the advanced space technology program in the agency with plans laid out in 14 draft technology roadmaps. It has been years since NASA has had a vigorous, broad-based program in advanced space technology development and its technology base has been largely depleted. However, success in executing future NASA space missions will depend on advanced technology developments that should already be underway. Reaching out to involve the external technical community, the National Research Council (NRC) considered the 14 draft technology roadmaps prepared by OCT and ranked the top technical challenges and highest priority technologies that NASA should emphasize in the next 5 years. This report provides specific guidance and recommendations on how the effectiveness of the technology development program managed by OCT can be enhanced in the face of scarce resources.
Keywords: Space and Aeronautics

Report of the Committee on a Commercially Developed Space Facility - National Research Council (The National Academies Press, 1989)
The Committee on a Commercially Developed Space Facility assessed the scientific and commercial benefit to the nation of having a CDSF in place prior to Space Station operations. The committee examined planned and anticipated microgravity research and manufacturing requirements of the federal government and commercial users as well as the extent to which existing, planned, and proposed capabilities and infrastructure could support these requirements. The committee's findings concentrate on the desirability of having an additional space facility in service to the interim preceding Space Station Freedom.
Keywords: Space and Aeronautics

Scientific Uses of the Space Shuttle (The National Academies Press, 1974)
Scientific Uses of the Space Shuttle focuses on those aspects of the Shuttle most different from conventional launch-vehicle capabilities. It especially considers the sortie mode, in which the Shuttle carries into orbit a payload that remains attached to the Shuttle and then returns to earth with the payload after one to four weeks. Interest in the sortie mode is particularly great because of the contemporary decision by several European countries to develop a space laboratory (Spacelab). The report also considers the use of the Shuttle for launching, servicing, and recovering satellites and for launching lunar, planetary, and interplanetary missions.
Keywords: Space and Aeronautics

Practical Applications of a Space Station - National Research Council (The National Academies Press, 1984)
The demonstrated capabilities of the Space Shuttle and rapid advancements in both ground- and space-based technology offer new opportunities for developing space systems for practical use, including a manned space station and one or more unmanned space platforms. The Space Applications Board conducted a study to determine the technical requirements that should be considered in the conceptual design of a space station and/or space platforms so that, if developed, these spacecraft would have utility for practical applications. Practical Applications of a Space Station is a formal report of the study, in which six panels met, one in each of the following areas: earth's resources, earth's environment, ocean operations, satellite communications, materials science and engineering, and system design factors. Each panel was asked to consider what practical applications of space systems may be expected in their particular areas beginning around 1990. The panels were also asked to identify technological progress that would need to be made and that should be emphasized in order for space systems with practical uses to have greater utility by the time a space station might be available.
Keywords: Earth Sciences

Human Factors in Long-Duration Spaceflight (The National Academies Press, 1972)
Human Factors in Long-Duration Spaceflight is a compilation of the findings of a study of the behavioral, psychological, physiological, and medical factors of manned space missions of up to two years' duration. The intent of the recommendations in the report is to indicate the blocks of research, roughly in order of priority, that will be most fruitful in the years ahead in coming to grips with the problems of long-duration missions. The report calls for research into a wide range of problems, from bioinstrumentation and automated physical examinations to small-group dynamics, development of objective performance tests, criteria for habitability, relation between brain waves and cognitive efficiency, and so forth—problems that are experienced by both the crew of a long-duration spaceflight and contemporary society on earth.
Keywords: Space and Aeronautics

Recapturing a Future for Space Exploration: Life and Physical Sciences Research for a New Era - National Research Council (The National Academies Press, 2011)
More than four decades have passed since a human first set foot on the Moon. Great strides have been made in our understanding of what is required to support an enduring human presence in space, as evidenced by progressively more advanced orbiting human outposts, culminating in the current International Space Station (ISS). However, of the more than 500 humans who have so far ventured into space, most have gone only as far as near-Earth orbit, and none have traveled beyond the orbit of the Moon. Achieving humans' further progress into the solar system had proved far more difficult than imagined in the heady days of the Apollo missions, but the potential rewards remain substantial. During its more than 50-year history, NASA's success in human space exploration has depended on the agency's ability to effectively address a wide range of biomedical, engineering, physical science, and related obstacles—an achievement made possible by NASA's strong and productive commitments to life and physical sciences research for human space exploration, and by its use of human space exploration infrastructures for scientific discovery. The Committee for the Decadal Survey of Biological and Physical Sciences acknowledges the many achievements of NASA, which are all the more remarkable given budgetary challenges and changing directions within the agency. In the past decade, however, a consequence of those challenges has been a life and physical sciences research program that was dramatically reduced in both scale and scope, with the result that the agency is poorly positioned to take full advantage of the scientific opportunities offered by the now fully equipped and staffed ISS laboratory, or to effectively pursue the scientific research needed to support the development of advanced human exploration capabilities. Although its review has left it deeply concerned about the current state of NASA's life and physical sciences research, the Committee for the Decadal Survey on Biological and Physical Sciences in Space is nevertheless convinced that a focused science and engineering program can achieve successes that will bring the space community, the U.S. public, and policymakers to an understanding that we are ready for the next significant phase of human space exploration. The goal of this report is to lay out steps and develop a forward-looking portfolio of research that will provide the basis for recapturing the excitement and value of human spaceflight—thereby enabling the U.S. space program to deliver on new exploration initiatives that serve the nation, excite the public, and place the United States again at the forefront of space exploration for the global good.
Keywords: Space and Aeronautics

Post-Challenger Evaluation of Space Shuttle Risk Assessment and Management (The National Academies Press, 1988)
After the Challenger accident on January 28, 1986, President Reagan established the Presidential Commission on the Space Shuttle Challenger Accident to investigate the accident and make recommendations for the safe recovery of the Space Transportation System (STS). Among its recommendations, the Commission called upon NASA to review certain aspects of its STS risk assessment effort and to identify items that needed improvement. It further recommended that an audit panel be appointed by the National Research Council to verify the adequacy of the effort. Post-Challenger Evaluation of Space Shuttle Risk Assessment and Management is the compilation of the conclusions and recommendations of the Committee on Shuttle Criticality Review and Hazard Analysis Audit. It is intended to assist NASA in taking the prudent additional steps which will provide a reasonable and responsible level of flight safety for the Space Shuttle, but has broader applications for other space programs.
Keywords: Space and Aeronautics

Defending Planet Earth: Near-Earth-Object Surveys and Hazard Mitigation Strategies - National Research Council (The National Academies Press, 2010)
The United States spends approximately $4 million each year searching for near-Earth objects (NEOs). The objective is to detect those that may collide with Earth. The majority of this funding supports the operation of several observatories that scan the sky searching for NEOs. This, however, is insufficient in detecting the majority of NEOs that may present a tangible threat to humanity. A significantly smaller amount of funding supports ways to protect the Earth from such a potential collision or "mitigation."
Keywords: Space and Aeronautics